ISOLASI DAN IDENTIFIKASI KOMPONEN KIMIA FRAKSI n-HEKSANA DAUN TUMBUHAN JERINGAU (Acorus calamus Linn.) - Ari Wahyuni; Abd Kadir; Ahmad Najib (As-Syifaa Jurnal Farmasi, 2012)
Isolation and identification of n-Hexane faction from Sweet Flag leaves (Acorus calamus Linn.) was done. The aim of research is determine the chemical compound on it leaf, which was commonly used as the traditional medicine. Sample from 250 grams of dried Sweet Flag leaf, macerate using methanol, produce 21.563 grams dried extract. Isolation of n-hexane faction  using  column  chromatography  method  with  various  mobile  phases.  The  isolate identified by UV and IR spectroscopy method. From the data result show that the isolate has a specific compound.Key words : Isolation, Acorus calamus, UV-Vis, IR